Answer:
bruh
Step-by-step explanation:
maybe google works
Multiply 2x-5y= -21 by 3 to make it 6x-15y= -63
Multiply 3x-3y= -18 by -5 to make it -15x+15y=90
This cancels the y’s out which leaves us with
6x=-63
&
-15x=90
x for 6x=-63 equals - 10.5 so x is - 10.5 and for -15x=90, x= -6
Then you plug in x into any equation you’d like to find y.
Let’s plug in - 10.5 into 6x... equation.
6(- 10.5)-15y=-63
63-15y= -63
-63 -63
-15y=0
y=0 and x= - 10.5. When you plug in this values it makes the equation true!
But the correct answer is the first one north. Sorry if I’m doing too much hahah
If I’m confusing here’s the right answer...
6x-15y= -63
-15x+15y=90
Answer:
c
Step-by-step explanation:
f(x) =10 (20)=200
Answer: 9h+40 (C)
Step-by-step explanation: the answer is 9h+40 because $9/hr rate is dependent on how many hours she worked (h), so it would be multiplied. She earned $40 already, so it would be added. the correct expression would be 9h + 40, or c.
Answer:
Solve for x by simplifying both sides of the equation, then isolating the variable.x≈−0.00413995,1.6090059
Step-by-step explanation: